2012
DOI: 10.1021/om300820b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Zr–CH2–Ph Bond Angles in Tetrabenzylzirconium: Analysis of Benzyl Ligand Coordination Modes

Abstract: Analysis of a monoclinic modification of Zr(CH 2 Ph) 4 by single-crystal X-ray diffraction reveals that the bond angles Zr−CH 2 −Ph in this compound span a range of 25.1°, which is much larger than previously observed for the orthorhombic form (12.1°). In accord with this large range, density functional theory calculations demonstrate that little energy is required to perturb the Zr−CH 2 −Ph bond angles in this compound. Furthermore, density functional theory calculations on Me 3 ZrCH 2 Ph indicate that bendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 81 publications
4
54
0
Order By: Relevance
“…It is well documented that electron deficient benzyl complexes of the early transition metals may distort in order to relieve electronic unsaturation via methylene C-H agostic and/or C 6 H 5 p-system interactions with the metal centre. [32][33][34][35] On inspection, the two benzyl ligands in 2 are bound in an asymmetric manner and inequivalent, as demonstrated by their markedly different Ti-CH 2 -C ipso angles [101.94 (15) and 115.23 (15)1] and Ti-C ipso distances [2.886(2) and 3.085(2) Å].…”
mentioning
confidence: 99%
“…It is well documented that electron deficient benzyl complexes of the early transition metals may distort in order to relieve electronic unsaturation via methylene C-H agostic and/or C 6 H 5 p-system interactions with the metal centre. [32][33][34][35] On inspection, the two benzyl ligands in 2 are bound in an asymmetric manner and inequivalent, as demonstrated by their markedly different Ti-CH 2 -C ipso angles [101.94 (15) and 115.23 (15)1] and Ti-C ipso distances [2.886(2) and 3.085(2) Å].…”
mentioning
confidence: 99%
“…Similarly, the average M–C–C ipso angle is 102° in Zr( L 1 ) 2 Bn 2 , and 124° in Hf( L 1 ) 2 Bn 2 . These parameters place the benzyl ligands in Zr( L 1 ) 2 Bn 2 at the border of the η 1 and η 2 coordination modes . The M–O bond lengths are also longer in Zr( L 1 ) 2 Bn 2 than in Hf( L 1 ) 2 Bn 2 , on average.…”
Section: Resultsmentioning
confidence: 69%
“…Strict assignment of the hapticity was often a fairly subjective issue until Parkin et al undertook an in-depth investigation into bonding in Zr-benzyl species. 48 This study revealed two ways of distinguishing the bonding mode of a benzyl ligand: first, the deviation of the M−CH 2 −Ph bond angle from the idealized 109.5°(which can identify between η 1 and higher hapticities) …”
Section: Organometallicsmentioning
confidence: 95%